Influence of Madrasah Head Leadership, Motivation and Madrasah Culture on Teacher Performance in Madrasah Aliyah Model 2 Medan - Amiruddin Siahaan; Tien Rafida; Khairunnisa Batubara (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
The purpose of this study was to determine: (1) the influence of madrasa head leadership on teacher performance; (2) the effect of motivation on teacher performance (3) the influence of madrasa culture on teacher performance; (4) the influence of madrasa head leadership and motivation on teacher performance in Madrasah Aliyah Negeri 2 Model. The study was conducted at Madrasah Aliyah Negeri 2 Model located on Wiliem Iskandar no. 7A Medan. This research is a quantitative study with a population of 149 people and a sample of 109 people who were determined using the Slovin method. The results showed that (1) there was a positive and significant influence between the leadership of the madrasah head on teacher performance; (2) there is a positive and significant effect between motivation on teacher performance. (3) there is a positive and significant influence between madrasa culture on teacher performance. (4) there is a positive and significant influence between madrasah head leadership and motivation on teacher performance. (5) there is a positive and significant influence between the leadership of the madrasa headmaster and madrasa culture on teacher performance. (6) there is a positive and significant influence between motivation and madrasa culture on teacher performance. (7) there is a positive and significant influence between madrasah head leadership, motivation and madrasa culture together on teacher performance. Madrasah headship leadership, motivation and madrasa culture have an effect on teacher performance by 53.4% and the remaining 46.6% is determined by other factors.